Toward an Ethnography of Mobile Tourism Industry Workers in Banff National Park - Smith, Angèle; Staveley, Jeremy (Anthropologica, 2014)
While there is much anthropological literature concerning transnational mobility and identity of migrants and refugees, tourists and even entrepreneurs, less explored is the great complexity of the many different factions within mobile worker communities of resort destinations. If it is unexpected that these tourism workers are understudied, it is even more surprising given that they are key agents in (re)producing the identity and character of the place, which they then "sell" to tourists. At the same time, the identity of tourism workers is profoundly shaped by their experiences. This article examines approaches for studying the experiences of travel, work and life in Banff National Park.